Conception of Managing Practices as Key Factor to Achieve Rural Development and Sustainability in Southern Brazil - Luis Augusto Araujo, Roberth Andrés Villazón Montalván; ntonio Marcos Feliciano, Alexandre Luís Giehl (European Journal of Sustainable Development, 2017)
Achievement of rural development under the three pillars of sustainability is a strenuous process that will depend on a set of complex variables. Defining actions to contribute to socioeconomic development requires the diagnosis of current conditions, facilitating the decision-making process by policy makers. In addition, purpose of rural establishments’ managers is to build up their future, then the greater their resilience to markets’ oscillation and environmental constrains the greater possibilities to achieve sustainability. Consequently, identifying the adopted managing practices by family farmers holding most of rural area is preponderant. Considering that management practices influence and are influenced by strategies that depend on external and internal environment conditions, then, how to understand the wide variety of activities that make up the management practice and the creation of strategies, as well as their perception by farmers? This paper aims to respond to it in a survey conducted in southern Brazil. The study was guided by the principles of qualitative and quantitative research, with exploratory and descriptive nature. It was applied a questionnaire to 232 families and then responses were evaluated under a refined SWOT analysis. Managers recognize the external environment variables as threats and the internal environment ones as a strength. Keywords: Emerging Countries, Economic Sustainability, Rural Development, Family Farming, Strategies, SWOT Analysis